RONC-07. Fractionated radiotherapy is required to accurately mimic neurostructural late effects in preclinical models. (3rd June 2022) - Whitehouse, Jacqueline; Howlett, Meegan; Buck, Jessica; Somers, Kale; Lawler, Jessica; Hii, Hilary; Carline, Brooke; Kuchibhotla, Mani; Sewoo, Bhedita; Rosenow, Tim; Feindel, Kirk; Ebert, Martin; et al.
Abstract: Pediatric brain cancer patients treated with fractionated radiotherapy commonly develop long-term late side-effects including cognitive deficits. Many preclinical models of late effects have been developed that use a single, high dose of radiotherapy, which does not mimic the fractionated schedule children receive clinically. This study aimed to create a mouse model of late effects using clinically-relevant fractionated radiotherapy, and to measure the effects on the developing brain. Juvenile mice were treated at postnatal day 16 with a single dose of 8Gy whole brain radiation, or a mathematically-equivalent fractionated dose of 18Gy (9 x 2Gy daily fractions). Sham control mice received a CT scan, or 9 x sham CT scans. Mice were allowed to grow to young adulthood (63 days). Ex vivo anatomical MRI scans were performed along with diffusion tensor imaging (DTI) and histology. Mice receiving a single 8Gy radiation dose exhibited significantly decreased volumes in areas including the olfactory bulbs (-19%), hippocampus (-7%), corpus callosum (-9%) and motor cortex (-9%). In contrast, mice receiving fractionated radiotherapy showed fewer significantly decreased regions, although olfactory bulbs were reduced (-12%). Furthermore, doublecortin-positive cells were significantly reduced in the dentate gyrus indicating profound effects of radiotherapy on murine neural stem cells. Few radiotherapy-induced differences were observed by DTI, and immunohistochemistry revealed no changes in myelin basic protein, suggesting that white matter is minimally altered in mice. These results show that preclinical models exhibit treatment-induced late effects, and that commonly-used experimental approaches of single dose radiotherapy induce more neurological changes than an equivalent fractionated dose, thus may over-estimate radiotherapy-induced late effects. We have developed a clinically-relevant fractionated dosing protocol in mice, which replicates late effects experienced by children, and can be used to measure long-term effects of novel chemo/radiotherapy treatment combinations, ensuring children with brain cancer receive treatment both effective and safe treatment.